The p53 orchestra: Mdm2 and Mdmx set the tone - Wade, Mark (2010)
The activities of p53 cover diverse aspects of cell biology, including cell cycle control, apoptosis, metabolism, fertility, differentiation and cellular reprogramming. Although loss of p53 function engenders tumor susceptibility, hyperactivation of p53 is lethal. Therefore, p53 activity must be strictly regulated to maintain normal tissue homeostasis. Critical for the control of p53 function are its two main negative regulators: Mdm2 and Mdmx. Recent reports have provided insight into the complex mechanisms that regulate these two proteins and have revealed novel functions for each. Here, we review and evaluate models of Mdm2- and Mdmx-dependent regulation of p53 activity. Both Mdm2 and Mdmx receive input from numerous signaling pathways and interact with many proteins in addition to p53. Therefore, we also consider roles for Mdm2 and Mdmx in additional cancer-related networks, including Notch signaling and the epithelial-to-mesenchymal transition.